Response to Communication on Rand-HUD Fire Models - Chaiken, Jan; Ignall, Edward; Kolesar, Peter; Walker, Warren (Management Science, 1980)
The Communication from Rodrick and Deborah Wallace repeats allegations that they have made in print [Wallace, D. 1977. New York city fire crisis, part one, the system is falling apart. Heights and Valley News (May) 10–11; Wallace, R., D. Wallace. 1977. Studies on the Collapse of Fire Service in New York City 1972–1976: The Impact of Pseudoscience in Public Policy (pamphlet), Univ. Press of America, Washington, D.C.] and in various forums for more than three years. Their critique is not of Chaiken's paper, “Transfer of Emergency Service Deployment Models to Operating Agencies,” (Chaiken, J. 1978. Transfer of emergency service deployment models to operating agencies. Management Sci. 24 (7) 719–731.) but rather they use the appearance of that paper as an occasion to comment again on the application of Rand's fire deployment models in New York City during the period from 1972 to 1976. Readers of Chaiken's paper who are not familiar with this history are likely to wonder how his paper, which barely mentions New York City, inspired the Wallaces' comments in this Communication.